Africa Continent of Economic Opportunirt - Fick, David; Kevin Humphrey, Monica Seeber, Angela McClelland,Nuwa Nyanzi, Adam Rumball, Mad Cow Studio, Jakaranda Printers (Johannesburg : STE Publishers, 2006)
Summary: The presents a number of case studies of small, medium and large business enterprises and community projects in Africa.
Not included
Adult
Keywords: South Africa